Effects of excessive or restricted phosphorus and calcium intake during early life on markers of bone architecture and composition in pigs. (17th March 2020) - Gerlinger, Christian; Oster, Michael; Reyer, Henry; Polley, Christian; Vollmar, Brigitte; Muráni, Eduard; Wimmers, Klaus; Wolf, Petra
Abstract: Sufficient supply of pigs with calcium (Ca) and phosphorus (P) is essential for animal health and welfare during the growth period. However, the P content in animal manure is considered as a cause of massive environmental problems in soil and aquatic ecosystems. To complement previous findings, the objective of this study is the investigation of effects of a reduced and increased Ca and P supplementation on bone mineralization and bone structure compared with the current dietary recommendation. Another aim is to find possible serum markers that would allow the assessment of adequacy of P supply for bone health during growth. The result validated that the recommended Ca and P supply is sufficient, without the addition of microbial phytases. However, addition of P has no further beneficial effects on bone stability, while P supplementation below the recommended level affects bone development and growth performance. Reduced P levels have consequences for cancellous bone density and trabecular architecture. Further fine‐tuning of the P supply in conjunction with an appropriate Ca supply will contribute to a reduction in P waste and associated environmental impact while maintaining animal health and welfare.